Pelatihan Manajemen Keuangan Bagi Ibu-Ibu PKK Pelaku UMKM dalam upaya Mewujudkan Keluarga Sejahtera - Rudi Sanjaya; Krida Puji Rahayu; Chandra Fitra A.; Nurmono Nurmono; Nely Isdiarti (Jurnal Abdi Masyarakat Humanis, 2022)
Our Community Service is collaborating with Ms. PKK as MSME actors in RT 01 RW 021 Parigi Lama Village, Pondok Aren District, South Tangerang City, which only a small part of entrepreneurship has been carried out both traditionally and has been done online. MSME business management is run as it is so that the results are inadequate. The lack of complete infrastructure has an impact on low entrepreneurial motivation. It is proven that only some partners have used digital media or online in their business. Likewise, the condition of the organization is not yet complete, still simple, still using a manual financial statement bookkeeping system, SOPs are not complete and have not been fully implemented, due to limited personnel and supporting facilities. The basic (priority) problem faced by partners is the problem of women in the recitation group/PKK RT 01 RW 021 Parigi Lama Village which is always discussed regarding financial management, namely the existence of places that are over budgeted so that there is a financial deficit at the end of the month or there are unmet needs. Based on the findings of this case, there is concern that the PKK's inability to manage finances can have fatal consequences for the business being developed and the finances used to meet daily needs.